Pengaruh profit sharing, inflasi, kurs dan BI rate terhadap kuantitas deposito mudharabah pada Bank Umum Syariah di Indonesia periode 2015-2019 - Nazmudin, Nandang; Mubarokah, Isroyatul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
New patterns of illegal or fraudulent capitalization have been proposed. in public fraud throughout 2019. The model in question is the concept of sharia capitalization in the form of anti-usury capitalization. seeing an increase in fraud capitalization. There were 80 in 2017, 108 in 2018, and 444 fraudulent capitalization entities investigated by the task force in 2019. One of the sharia capitalizations that are said to be fraudulent capitalizations is the plantation capitalization of Kampung Kurma. In this research, what will be discussed is the impact of profit sharing, inflation, exchange rates, and BI interest rates on total deposits in Mudharabah. This research has purpose to know influence of Profit sharing, Inflation, Exchange Rate,and BI Rate on The Amount of Mudharabah Deposits in Sharia Commercial Ban contained in the Financial Service Authority.. The period of this research is 5 (fiver) years, starting from 2015 until 2019.The design of this research is applied research. The population in this research includes Islamic Commercial Bank wich are included in State-Owned Enterprises (BUMN) during the 2015 until 2019. The sampling technique used was purposive sampling and research data as many as 44 of 3 (tree) sample companies. The data analysis method used is multiple linear regression using SPSS version 21.00 and Microsoft Excel 2019.The result showed that Profit sharing, Inflation, Exchange Rate,and BI Rate are selamaeously not effect significantly on The Amount of Mudharabah Deposits to the value significance of 0,781, 0,375, 0,091 and 0,450.